Gender gaps in agricultural growth and development: Opportunities for improving gender-responsive programming - Blackmore, Ivy; Ringler, Claudia; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2022)
In addition to identifying gender gaps and other challenges and opportunities for entrepreneurship in agricultural growth and development, this brief focuses on potential for improvement in the key areas of (1) seed systems, (2) finance and market access, and (3) production and value chains. While gender norms and challenges are inherently context-specific, the underlying intention of this evidence brief is to provide an overview of research findings from low- and middle-income countries, to address key questions and challenges that can be generalized across contexts, and to offer suggestions of promising approaches and best practices.